Impact of credit control techniques on revenue collection and financial performance of a firm: a case of NEC Agriculture - Mambiri, Loraine (Midlands State University, 2018)
This study aims to assess the impact of credit control techniques on revenue collection and financial performance of the firm using NEC Agriculture as the case study. The objectives of the study were to assess the impact of credit control techniques on revenue collection and financial performance, to assess the cost associated with credit control techniques against the revenue collected and also to compare the credit control techniques implemented in other countries or organizations to those used by NEC Agriculture so as to draw lessons vital for more revenue collection and improved financial performance. Descriptive and Case study research design were used. Judgmental sampling technique was used on a sample size of 17 employees out of an entire population of 40 employees. Questionnaires were administered to the 17 respondents of which 16 were completed and returned. In addition 6 top management employees were interviewed for data collection. The findings of the study showed that the current credit control techniques of NEC Agriculture were partially implemented and also they had a positive impact on revenue collection and financial performance. It also revealed that there is an inverse relationship between costs associated with credit control techniques against revenue collected. The study concluded that credit control techniques had the greatest impact on revenue collection and financial performance, followed by the costs associated with credit control techniques and other factors such as the economic instability and political interventions. This study recommended the introduction of credit policies, online billing systems, upgrading of the pastel system and creation of website for information dissemination to the farming entities.